Determinants of Income Inequality in Indonesia - Hanif Arif Baskoro; Dwi Budi Santoso; Farah Wulandari Pangestuty (Proceedings of the 1st International Conference on Social Science (ICSS), 2024)
Indonesia's elevation to an upper-middle-income country in 2019 still leaves unresolved issues of income inequality. While the Indonesian government has implemented several policies to address this, the spatial aspects have not been adequately considered. This study utilizes panel data from 34 provinces in Indonesia over the period 2018-2020 to identify the determinants of income inequality and examine the presence of regional spatial connections influencing income inequality. The findings reveal that per capita income and foreign direct investment have a negative relationship with income inequality, whereas exports and imports have a positive relationship. Additionally, there is no evidence of spatial linkages between regions affecting income inequality. These insights suggest that policies aimed at reducing income inequality should focus more on economic factors rather than spatial considerations.